Tagish Indian known as Tagish Charley with dogsled, Alaska, ca. 1898 - Hegg, Eric A., 1867-1948
Man with loaded dog sled, moving through snow, ca. 1897-1900. Caption on image: 687. "Tagish Charley" a noted Indian on his way to Tagish. E. A. Hegg Note from unidentified sources: Tagish Charlie, gold prospector